1999
DOI: 10.1002/(sici)1096-9071(199909)59:1<73::aid-jmv12>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Four new genotypes of adenovirus type 3 isolated from patients with conjunctivitis in Japan

Abstract: Adenovirus type 3 (Ad3) was the most frequently isolated serotype from patients with conjunctivitis during the period from 1989 to 1991 in Japan. All Ad3 strains isolated in 1990 had an identical genotype, Ad3f. However, in 1992, the predominant serotype was replaced by Ad4. The genome type was examined to determine whether genetic changes existed in Ad3 isolates in 1992. Ad3 isolated from 55 patients with acute conjunctivitis during the period from June 1992 to February 1993 in Japan was assessed by genome ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…First, many more genome types were observed during our 12-year study than were observed in the previous reports (2, 13, 14, 21, 22, 26), and the genome types in our study appeared to be closely related to each other. Second, the hexon and fiber sequences changed in conjunction with alternations in the genome type, and significant transitions in genome types were observed for HAdV-37, as with other serotypes (1,10,15,16,20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, many more genome types were observed during our 12-year study than were observed in the previous reports (2, 13, 14, 21, 22, 26), and the genome types in our study appeared to be closely related to each other. Second, the hexon and fiber sequences changed in conjunction with alternations in the genome type, and significant transitions in genome types were observed for HAdV-37, as with other serotypes (1,10,15,16,20).…”
Section: Discussionmentioning
confidence: 99%
“…Since 1989, however, very few reports about HAdV-37 genome types have appeared. In other serotypes, genome type analysis and long-term surveillance have been actively pursued (1,10,15,16,20). The resulting reports suggested an association between clinical epidemiology and changes in genome types.…”
mentioning
confidence: 99%
“…In the report of Itakura et al, the genome types of Ad3 isolated during two consecutive epidemics of keratoconjunctivitis were different (12). Itoh et al suggested that the emergence of new Ad3 genome types may contribute to the replacement of prior adenovirus serotypes associated with conjunctivitis (13). The nationwide epidemic of Ad7 in Japan in 1995 to 1998 occurred with the emergence of Ad7d2 in a setting of lowgrade activity of Ad7d during the preceding years (23).…”
Section: Discussionmentioning
confidence: 99%
“…Gel banding patterns were analyzed with Quantity One version 4.3.1 software (Bio Rad, Hercules, CA) with Gel Doc transillumination. Resultant banding profiles were then compared to data from previously published HAdV3 characterizations 1,10,11…”
Section: Methodsmentioning
confidence: 99%
“…HAdVs also cause conjunctivitis, gastrointestinal and urinary tract infections, and occasionally encephalitis 1. HAdV infections may be particularly severe among young children and the immunocompromised.…”
Section: Introductionmentioning
confidence: 99%